PEMANFAATAN BERBAGAI DOSIS SERBUK GERGAJI UNTUK MENINGKATKAN UMUR SIMPAN BENIH KAKAO (Theobroma cacao L.) - Umroh Umroh; Rosmalinda Rosmalinda; Nurhayati Nurhayati; Sarwendah Ratnawati Hermanto; Venti Jatsiyah (Politeknik Negeri Ketapang, 2022)
Cocoa seeds are seeds that have easy germination properties or are called recalcitrants. The technique of storing recalcitrant seeds cannot be dried below a critical moisture content, germinates easily and is not tolerant of low temperatures, so it is necessary to modify storage using sawdust storage media so that the seeds remain of good quality. The purpose of this study was to determine the effect of various doses of sawdust on the shelf life of cocoa seeds. Besides that, it also knows the best treatment of various doses of sawdust that can increase the shelf life of cocoa seeds. This study used a completely randomized design (CRD) with 6 treatments and 6 replications so that there were 36 experimental units. Parameters observed consisted of seed moisture content during storage, moldy seeds in storage and percentage of germination in seeding. Observational data were analyzed using ANOVA. If the results have a significant effect, then continue with the Duncan Multiple Range Test (DMRT) test at a level of 5%. The results showed that the best sawdust storage medium was 180 grams (A5) which could reduce the percentage of moldy seeds in storage.